Dynamic Analysis on the Determinants of Prevalence of Undernourishment in Indonesia: A System GMM Approach - Geubrina, Yulia; Suriani, Suriani; Seftarita, Chenny (Signifikan: Jurnal Ilmu Ekonomi, 2025)
Research Originality: This original study examines the determinants of undernourishment in Indonesia with mediating variables.Research Objectives: This study examines the impact of food production, inflation, unemployment, and social food assistance on undernourishment with people's purchasing power as a mediating variable.Research Methods: Dynamic panel analysis with the Generalized Method of Moment (GMM) and Sobel test examines direct and mediation relationships for the data period 2018-2023.Empirical Results: The results show the direct and indirect effects of inflation, unemployment, and social food assistance on the prevalence of undernourishment in Indonesia through the mediation of people’s purchasing power. Meanwhile, food production has no effect either directly or indirectly.Implications: This study implies that the government must maintain stable inflation, create jobs, effectively target food assistance, and reduce reliance on social food assistance.JEL Classification: C31, G21, I32, O18How to Cite:Geubrina, Y., Suriani., & Seftarita, C. (2025). Dynamic Analysis on the Determinants of Prevalence of Undernourishment in Indonesia: A System GMM Approach. Signifikan: Jurnal Ilmu Ekonomi, 14(1), 111-130. https://doi.org/10.15408/sjie.v14i1.42524.